Геохимические особенности рудных формаций Алтае-Саянской складчатой области - Рихванов Л. П. Леонид Петрович; Сарнаев С. И.; Комарницкий Г. М.; Поцелуев А. А. Анатолий Алексеевич; Анцырев А. А.; Арбузов С. И. Сергей Иванович; Ершов В. В. Василий Владимирович; Меньшиков В. С.; Язиков Е. Г. Егор Григорьевич (1987, 1987)
В фонде НТБ ТПУ отсутствует